Pengaruh Kualitas Pelayanan Akademik dan Fasilitas Pendukung Pembelajaran Terhadap Kepuasan Masasiswa Universitas Islam Negeri Sumatera Utara (Studi Kasus Mahasiswa FEBI) - Afdolli Ilman Ritonga; Dini Lestari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to examine whether the quality of academic services and learning support facilities have an effect both jointly and partially on student satisfaction in the Faculty of Islamic Economics and Business (FEBI) at the State Islamic University of North Sumatra. The population in this study were all students of the Islamic Faculty of Economics and Business, the number of which cannot be known. The number of samples taken was 100 students using the Proportionate Stratified Random Sampling technique. The data collection instrument used was a questionnaire using a Likert scale which was compiled based on constructs summarized from various theories which were embodied in operational variables, while testing the research instruments was carried out through validity and reliability tests. Data analysis was carried out through a requirements test consisting of a normality test, multicollinearity test and heteroscedasticity test. Hypothesis testing was carried out using multiple linear regression analysis. The results showed that there was an influence on the quality of academic services and educational facilities on student satisfaction in the Faculty of Islamic Economics and Business at the State Islamic University of North Sumatra.